Transformational agroecology across food, land and water systems - Alliance of Bioversity International and CIAT (2022)
The CGIAR initiative Transformational Agroecology Across Food, Land and Water Systems will engage with food system actors in seven countries (Burkina Faso, India, Kenya, Lao PDR, Peru, Tunisia, and Zimbabwe) to find better ways of putting into practice the 13 agroecological principles listed in this brochure.